Investigation into the release of nanomaterials from can coatings into food. (June 2018) - Bott, Johannes; Störmer, Angela; Albers, Peter
Highlights: Simultaneous investigation of eight nanomaterials used in food can coatings. Combination of AF4/MALLS and ICP-MS allowed particle- and element-specific detection. No release of nanomaterials used as additives in can coatings. Abstract: In this study internal and seam covering coatings as used in food cans were investigated on their potential to release nanomaterials (pigments, fillers) when food is stored and processed (sterilised) within coated cans. Two interior lacquers based on epoxy- and polyester- (with and without bisphenol A) resins and two seam covering coatings were used as lacquer matrices covering typical lacquer formulations. Eight different nanomaterials (four pigments and four fillers) were investigated that are typically used for adjusting colour and enhancing thermal and mechanical stability of the coatings. Aqueous sodium dodecylsulfate surfactant solution showed best suitability to disperse the nanomaterials with sufficient stability. A stable multi-nanomaterial dispersion, containing all eight nanomaterials at the same concentration each, was successfully used to develop an analytical method based on asymmetric flow filed-flow fractionation (AF4) coupled with multi angle laser light scattering (MALLS) detection and inductively coupled plasma mass spectrometry (ICP-MS) that allowed screening for possibly migrating nanomaterials at a limit of detection of 0.5 mg/dm 2 . Coated metal plates were brought in contact with the aqueous surfactant solution as alternative food simulant for 2 h at 130 °C (sterilisation) followed by for 10 days at 60 °C (long-term storage). Via AF4/MALLS measurements the release of small oligomeric components from internal coating formulations was detected. However, the particle- and element-specific detection system demonstrated the none-migration of nanomaterials (fillers or pigments) from all test samples.